Democratic Transition in Local Indonesia: An Overview of Ten Years Democracy - Lay, Cornelis (Jurnal Ilmu Sosial dan Ilmu Politik, 2012)
This article attempts to map out the current situation of democracy in Indonesia, especially at local levels. This map is based on a simple question: the extent to which 10 years of the democratization process in Indonesia has led the country closer towards effective democratic governance. It concludes that an effective democratic government is far from being realized. Moreover, this article shows a paradox in the development of local politics in Indonesia, on the one hand there has been political liberalization which is assumed as a prerequisite for the realization of democratic governance, but on the other hand, the development of local democracy in Indonesia seemed to stop at its infancy stage. The reasons behind this failure are vary, but in principle related to the symptoms that some scientists called as a "broken linkage" a syndrome in which the forces of modern intermediary fails to perform its functions in linking demos with public affairs.